2016
DOI: 10.1108/jeas-09-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Board governance, intellectual capital and firm performance

Abstract: Purpose – The purpose of this paper is to examine the relationship between the combined (multiplicative) effect of board governance and intellectual capital (IC) on firm performance. Design/methodology/approach – This study is cross-sectional and follows a positivist view of testing pre-specified hypotheses. The study uses a respondent sample of 128 service firms operating in Kampala, directors or managers are the unit of enquiry. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(94 citation statements)
references
References 77 publications
10
80
1
3
Order By: Relevance
“…The results in this study are consistent with research conducted by Nkundabanyanga (2016), which states that intellectual capital positively, and significantly affect the company's financial performance. These results are also supported Khan et al, (2012) which states that there is significant influence of intellectual capital that is also calculated using the method VAIC on the financial performance of the Bank in Pakistan.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The results in this study are consistent with research conducted by Nkundabanyanga (2016), which states that intellectual capital positively, and significantly affect the company's financial performance. These results are also supported Khan et al, (2012) which states that there is significant influence of intellectual capital that is also calculated using the method VAIC on the financial performance of the Bank in Pakistan.…”
Section: Resultssupporting
confidence: 82%
“…Ulum, Ghozali, and Purwanto, (2014), who analyzes the M-VAIC to measure the performance of the banking sector in Indonesia also found that Value Added is a function of capital employed and Intellectual Capital thus affecting the performance of the banking system. Nkundabanyanga (2016) found a positive relationship between the interactions of the elements of intellectual capital to financial performance observed in microfinance companies in the State Uganda. Based on some of the above description, it can be hypothesized as follows:…”
Section: The Proportion Of Chinese Ethnic In the Board Of Directors Amentioning
confidence: 99%
See 1 more Smart Citation
“…Precisely, we principally report on the differences of the board member age composition and the effect that it has on financial performance. While good financial performance is a target of every rational business enterprise, many enterprises both in developing and developed economies have had challenges of poor financial performance (Nkundabanyanga, 2012;Kamukama, 2011;Baisi, 2008). Financial performance is seen in different contexts but generally, it can be measured in terms of liquidity, capital growth, asset base, return on assets and return on investment (Martin, 2013;Hofmann & Lampe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even then, most studies mainly tested listed firms in a developed economy context thus side lining the private manufacturing sector in a developing economy perspective. As a result, poor financial performance has largely remained unexplained in the context of the developing economies especially in the Ugandan manufacturing sector (Nkundabanyanga, 2012;Mutambi, 2011). Most firms in the manufacturing sector have registered a low return on investment, low return on assets and some of them fail to maintain adequate liquidity levels (Ishengoma & Kapel, 2008).…”
Section: Introductionmentioning
confidence: 99%